Compósitos de polipropileno com fibra e nanofibrilas celulósicas preparados com auxílio da pulverização por cisalhamento no estado sólido - S3P - Oliveira, Gean Henrique Marcatto de (Universidade Federal de São Carlos, 2017)
In this study, polypropylene (PP) compounds were prepared using three types of cellulose fiber, pulp fiber (CF), cellulose nanofibrils (CNF) and lignocellulosic nanofibrils (LCNF) extracted from Eucalyptus grandis. The cellulosic fiber content of the compounds ranged from 10 to 30% by weight. Polypropylene grafted with maleic anhydride (PP-g-MAH) was also used as a compatibilizer. The solid state shear pulverization technique (S3P) was employed with the aim of improving the blending and dispersion of fibers in the matrix and a comparison with the compounds containing freeze dried nanofibrils (FD) was performed. X-ray diffraction (XRD) was used to measure the crystallinity index of cellulosic fibers, as well as scanning electron microscopy (SEM) was used for morphological characterization. With the aid of the modules processed by S3P, the PP / FC 70/30 sample presented results in the best mechanical tensile results, with a 100% increase in tensile strength and 75% in Young's modulus in relation to PP pure. Agglomerated was observed by scanning electron microscope with dimensions around 200 μm in the composites with nanofibrils (NFC and NFLC). Formulas with 30% by mass of cellulosic fibers- FD (FC, NFC and NFLC) were processed directly by solid state extrusion (MSE) for comparison with an S3P technique. The composite PP / FC 70/30 was released by S3P was released at 10% over time and the impact at the same time was 15% lower than the composite processed directly by extrusion in the molten state, while samples containing nanofibrils (NFC and NFLC) their independent traction and impact properties are not subjected to the S3P technique. The S3P technique is viable in the preparation of composites with the cellulosic fibers in the presence of water, keeping the mechanical and morphological properties similar to the composites prepared with lyophilized nanofibrils.
Composites of polypropylene with fiber and nanofibrils prepared with assisted by solid state shear pulverization - SSSP
Keywords: Nanofibrilas de celulose; Fibras de celulose; Pulverização por cisalhamento no estado sólido; Liofilização; Cellulose nanofibrils; Cellulose fibers; Solid-state shear pulverization; Freeze drier; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA